Firearms-related skeletal muscle trauma: pathophysiology and novel approaches for regeneration - Anselmo Moriscot (Nature Portfolio, 2021)
Abstract One major cause of traumatic injury is firearm-related wounds (i.e., ballistic trauma), common in both civilian and military populations, which is increasing in prevalence and has serious long-term health and socioeconomic consequences worldwide. Common primary injuries of ballistic trauma include soft-tissue damage and loss, haemorrhage, bone fracture, and pain. The majority of injuries are of musculoskeletal origin and located in the extremities, such that skeletal muscle offers a major therapeutic target to aid recovery and return to normal daily activities. However, the underlying pathophysiology of skeletal muscle ballistic trauma remains poorly understood, with limited evidence-based treatment options. As such, this review will address the topic of firearm-related skeletal muscle injury and regeneration. We first introduce trauma ballistics and the immediate injury of skeletal muscle, followed by detailed coverage of the underlying biological mechanisms involved in regulating skeletal muscle dysfunction following injury, with a specific focus on the processes of muscle regeneration, muscle wasting and vascular impairments. Finally, we evaluate novel approaches for minimising muscle damage and enhancing muscle regeneration after ballistic trauma, which may have important relevance for primary care in victims of violence.